MAGAZINE COVER SEMIOTICS ANALYSIS IN PRINTED MEDIA: ARTICLE REVIEW THROUGH ACADEMIC DATABASE - Kurnia Aljufri; Irmawan Rahyadi (Jurnal Ekonomi, 2022)
The front cover of a magazine has meaning that deserves to be analyzed more deeply and becomes one of the attractiveness factors that show the characteristics of a magazine so that readers can easily identify the magazine. In this article, the researcher presents a systematic review of articles on semiotic analysis of magazine covers contained in journal articles that have been published in the academic database. This study aims to enable readers to easily find, summarize, organize, and synthesize information about semiotic analysis of magazine covers in print media. This study follows a systematic article review method, the researcher has set 3 research questions and 75 scientific articles that answer these questions. Therefore, this study conducted a systematic review and synthesized empirical findings on semiotic analysis of magazine cover images through the academic databases of SAGE Journals, Taylor & Francis, and Wiley Journal from 2016 to 2021. The researcher found that the literature on this topic is broad and diverse with contributions from various disciplines and theoretical and methodological approaches. Based on the researcher's findings, the journals that publish the most are the Visual Communication Journal with 15 Research Articles and Social Semiotics with 14 Research Articles which are dominated by Western countries such as UK, Denmark, Italy, Sweden and USA. The dominant method applied is Semiotics from various models such as Semiotic Chandler's model, Semiotic Charles Sanders Pierce, and Social Semiotic. In this semiotic analysis, we study things that are related to signs. It is hoped that the results of this research can contribute to the study of communication science and provide references for researchers who can enrich the results of a study using the semiotic analysis method and can be used as insight and knowledge in understanding the meaning conveyed on the cover of a magazine.